تقييم كفاءة طريقة تغطية غراس الحمضيّات بالأقمشة المعاملة بمحاليل المبيدات في مكافحة الأكاروس الأحمر ذي البقعتين Tetranychus urticae Koch (Acari: Tetranychidae) - صقر, إبراهيم (Latakia University Journal -Biological Sciences Series, 2018)
نفذت تجربة حقليّة لاختبار فاعليّة مبيدات الدايمثوات، الكبريت الميكروني والأبامكتين تجاه الأكاروس الأحمر ذو البقعتين T.urticae على غراس حمضيات صنف يافاوي بعمر 6 سنوات في مشتل الجامعة في الفترة الممتدة من نيسان إلى تموز 2017، باستخدام طريقة تغطية الغراس بأقمشة مشبعة بمحاليل 4 مبيدات هي: دايمثوات (حشري أكاروسي), أبامكتين (حشري أكاروسي), كبريت ميكروني (فطري أكاروسي), وبروبارجيت (أكاروسي متخصص) واستعمل المركب بروبارجيت كمبيد قياسي وضمن الظروف (حرارة 28 ± 4 ْم ورطوبة نسبيّة 75 ± 5%). كانت الفاعلية الأولية بعد 24 ساعة للمركبات الثلاث جيدة، وتفوّق الدايمثوات والكبريت معنويّاً على الأبامكتين، كما تفوق الدايمثوات معنوياً على البروبارجيت، وربّما يعود ذلك إلى تسامي الدايمثوات وأبخرة الكبريت. ازدادت درجة التأثير في اليومين الثاني والثالث للتجربة، وتجاوزت بالمتوسّط 56% عند نهاية التجربة مع كافّة المبيدات المستخدمة، ومع تفوّق معنوي للبروبارجيت (74.01% ) على الجميع، تلاه الدايمثوات 65.98% وبتفوّق معنوي على الكبريت والأبامكتين الّذين ظلت الفروق بينهما ظاهريّة عند نهاية التجربة. أظهرت التجربة تأثيراً جيّداً للمبيدات غير المتخصّصة (دايمثوات، كبريت ميكروني) التي تعطي أبخرة وغازات، مقارنة بالمبيد ذي المنشأ الطبيعي الطبيعي أبامكتين، وكانت نتائج المبيدات المدروسة جيّدة مقارنةً بالمبيد القياسي. A field experiment was conducted to examine the efficacy of the Dimethoate, Sulphur, Abamectin pesticides against T. urticae on citrus plants, by using pesticide-treated nets. Probargite was used as a standard pesticide. The experiment took place on 6 years old jaffa plants in the university plant nursery during the summer of 2017 within the conditions (temperature 28 ± 4 ˚C, relative humidity 75 ± 5%). Initial efficacy after 24 hours was good for the three compounds. Dimethoate and Sulphur significantly outperformed Abamectin, and Dimethoate outperformed Probargite as well, this can be attributed to volatility of Dimethoate and Sulphur fumes. The level of effect increased during the second and third days, and reached an average of 56% at the end of the experiment considering all of the used pesticides, with significant superiority of Probargite among all others (74.01%), and Dimethoate as the second (65.98%) significantly outperformed Sulphur and Abamectin between which the differences were not significant by the end of the experiment. The experiment showed a good effect of the unspecialized compounds (Dimethoate and Sulphur) that release vapors and gases on the natural compound Abamectin, and the results of the examined pesticides were good compared to the standard pesticide.